DESERTIFICATION AND LAND DEGRADATION IN KAZAKHSTAN - Issanova, G.; Saduakhas, A.; Abuduwaili, J.; Tynybayeva, K.; Tanirbergenov, S. (Scientific Journal of Pedagogy and Economics, 2020)
Desertification and land degradation are common processes in arid and semi-arid regions of Kazakhstan, especially southern parts, where areas are covered by a great variety of desert types. In deserts, soil-forming processes take place in conditions of severe water shortage, and high level of soil degradation and desertification. The main natural factors for these processes are a flat terrain, a high degree of arid climate, soil salinity, carbonate content, a lack of structure and low natural soil fertility. However, the anthropogenic factors of desertification and soil degradation became dominant last decades. The study considers the actual problems of natural and anthropogenic factors of desertification and land degradation within Kazakhstan. The desertification of huge territories is accompanied by soil contamination, waterlogging by surface water and groundwater, soil salinization, erosion (water, wind), degradation of vegetation cover, dehumidification and a decrease in general regional biological capacity. Analysis of the current status of the soil cover has shown intensive land degradation 43 % of the territory of Kazakhstan is subjected to degradation in significant degree; over 14 % of pastures have reached an extreme degree of degradation or are completely degradated. The Aral Sea region, Northern Caspian Sea and Southern Balkhash deserts can be observed as areas of intensive soil desertification, salinization and deflation processes. As well as the desertification process are progressing in the irrigated soils of the deltas of Syrdarya, Shu, Ile and Karatal rivers.